A Fast Prediction Method for Stability Safety and Reliability of Reservoir Bank Rock Slopes Based on Deformation Monitoring Data - Han, Zhang; JianKang, Chen; Jian, Kou Qing; Liang, Pei; Huibao, Huang (Frontiers in Earth Science, 2022)
The stability of the reservoir bank slopes is critical to the engineering operation's safety. Due to the complexities of geological conditions, the monitoring mode based on the deformation monitoring data cannot directly respond to the structural damage stability state, whereas the anther mode based on structural calculation is time-consuming and lacks real-time capabilities. To that end, this paper proposes a method to constructing a fast prediction of the safety state of reservoir bank rock slope based on the physical significance of time-dependent deformation and rock creep at monitoring points, with the safety coefficient and reliability obtained by numerical calculation as the dependent variables and the slope deformation monitoring sequence as the independent variables, based on full verification of the rationality of numerical calculation. The model may be used to forecast the stability and reliability coefficients of reservoir bank slopes online using deformation data from the fild. The application verification of the left bank slope of the Dagangshan arch dam reveals that the average and maximum error of slope stability safety coefficient prediction is within 5% for 90 and 180 days, and the average and maximum error of reliability index prediction is within 10%, which meets the engineering requirements and can provide a new way for rapid prediction of slope engineering safety.